Recovery of Salivary Function: Contralateral Parotid-sparing Intensity-modulated Radiotherapy versus Bilateral Superficial Lobe Parotid-sparing Intensity-modulated Radiotherapy. Issue 9 (September 2016) - Miah, A.B.; Gulliford, S.L.; Morden, J.; Newbold, K.L.; Bhide, S.A.; Zaidi, S.H.; Hall, E.; Harrington, K.J.; Nutting, C.M.
Abstract: Aims: To establish whether there is a difference in recovery of salivary function with bilateral superficial lobe parotid-sparing intensity-modulated radiotherapy (BSLPS-IMRT) versus contralateral parotid-sparing IMRT (CLPS-IMRT) in patients with locally advanced head and neck squamous cell cancers. Materials and methods: A dosimetric analysis was carried out on data from two studies in which patients received BSLPS-IMRT (PARSPORT II) or CLPS-IMRT (PARSPORT). Acute (National Cancer Institute, Common Terminology Criteria for adverse events – NCI CTCAEv3.0) and late (Late Effects of Normal Tissue- subjective, objective, management analytical – LENTSOMA and Radiation Therapy Oncology Group) xerostomia scores were dichotomised: recovery (grade 0–1) versus no recovery (≥grade 2). Incidence of recovery of salivary function was compared between the two techniques and dose-response relationships were determined by fitting dose-response curves to the data using non-linear logistic regression analysis. Results: Seventy-one patients received BSLPS-IMRT and 35 received CLPS-IMRT. Patients received 65 Gy in 30 fractions to the primary site and involved nodal levels and 54 Gy in 30 fractions to elective nodal levels. There were significant differences in mean doses to contralateral parotid gland (29.4 Gy versus 24.9 Gy, P  < 0.005) and superficial lobes (26.8 Gy versus 30.5 Gy, P  = 0.02) for BSLPS and CLPS-IMRT, respectively. Lower risk of long-term ≥grade 2 subjective xerostomia (LENTSOMA) was reported with BSLPS-IMRT (odds ratio 0.50; 95% confidence interval 0.29–0.86; P  = 0.012). The percentage of patients who reported recovery of parotid saliva flow at 1 year was higher with BSLPS-IMRT compared with CLPS-IMRT techniques (67.1% versus 52.8%), but the difference was not statistically significant ( P  = 0.12). For the whole parotid gland, the tolerance doses, D50, were 25.6 Gy (95% confidence interval 20.6–30.5), k  = 2.7 (0.9–4.5) (CLPS-IMRT) and 28.9 Gy (26.1–31.9), k  = 2.4 (1.4–3.4) (BSLPS-IMRT). For the superficial lobe, D50 were similar: BSLPS-IMRT 23.5 Gy (19.3–27.6), k  = 1.9 (0.5–3.8); CLPS-IMRT 24.0 Gy (17.7–30.1), k  = 2.1 (0.1–4.1). Conclusion: BSLPS-IMRT reduces the risk of developing high-grade subjective xerostomia compared with CLPS-IMRT. The D50 of the superficial lobe may be a more reliable predictor of recovery of parotid function than the whole gland mean dose. Highlights: Two different parotid gland sparing IMRT techniques are described. Bilateral superficial lobe parotid sparing IMRT may reduce high grade xerostomia compared to contralateral parotid sparing IMRT.